2022
DOI: 10.3390/s22072592
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Principle of Taste Sensors to Detect Non-Charged Bitter Substances by 1H-NMR Measurement

Abstract: A taste sensor with lipid/polymer membranes is attracting attention as a method to evaluate taste objectively. However, due to the characteristic of detecting taste by changes in membrane potential, taste sensors cannot measure non-charged bitter substances. Many foods and medicines contain non-charged bitter substances, and it is necessary to quantify these tastes with sensors. Therefore, we have been developing taste sensors to detect bitter tastes caused by non-charged substances such as caffeine. In previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Consequently, this returned H + leads to an increase in surface charge density, resulting in an increase in membrane potential. The binding of 2,6-DHBA with caffeine has been confirmed by 1 H-NMR measurement [54]. This novel sensor also has been studied to detect other non-charged bitter substances for medicine, such as theophylline [55].…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Consequently, this returned H + leads to an increase in surface charge density, resulting in an increase in membrane potential. The binding of 2,6-DHBA with caffeine has been confirmed by 1 H-NMR measurement [54]. This novel sensor also has been studied to detect other non-charged bitter substances for medicine, such as theophylline [55].…”
Section: Introductionmentioning
confidence: 80%
“…Detection of Umami Substances Using Taste Sensors Treated with 2,6-DHBA and 2,6-DHTA First, we employed 2,6-DHBA and 2,6-DHTA as modifies to detect umami. These two materials were utilized to detect non-charged bitterness substances in previous studies [49,[53][54][55]. In contrast to the structure of 2,6-DHBA, which features only one carboxyl group on the benzene ring, 2,6-DHTA contains two carboxyl groups on the para-position of the benzene ring.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results obtained from the taste sensor and 1 H NMR analysis for the five modifiers are presented in Table 3 . 61 ) It was observed that caffeine interacts with all three HBAs and resorcinol, but the sensor modified with 2,6-DHBA exhibited a substantial response. The membrane potential change was moderate with 2-HBA and almost negligible with 3,5-DHBA, as shown in Table 3 .…”
Section: Taste Sensor Based On Allostery For Noncharged Substancesmentioning
confidence: 98%
“…We conducted nuclear Overhauser effect spectroscopy (NOESY) measurement to identify the type of bond formed in the interaction. 61 ) We can predict that caffeine and 2,6-DHBA have a stacked structure as shown in Fig. 9 by taking into account two facts, i.e.…”
Section: Taste Sensor Based On Allostery For Noncharged Substancesmentioning
confidence: 99%